P130Cas Src-binding and substrate domains have distinct roles in sustaining focal adhesion disassembly and promoting cell migration. - Leslie M Meenderink; Larisa M Ryzhova; Dominique M Donato; Daniel F Gochberg; Irina Kaverina; Steven K Hanks (PLoS ONE, 2010)
The docking protein p130Cas is a prominent Src substrate found in focal adhesions (FAs) and is implicated in regulating critical aspects of cell motility including FA disassembly and protrusion of the leading edge plasma membrane. To better understand how p130Cas acts to promote these events we examined requirements for established p130Cas signaling motifs including the SH3-binding site of the Src binding domain (SBD) and the tyrosine phosphorylation sites within the substrate domain (SD). Expression of wild type p130Cas in Cas -/- mouse embryo fibroblasts resulted in enhanced cell migration associated with increased leading-edge actin flux, increased rates of FA assembly/disassembly, and uninterrupted FA turnover. Variants lacking either the SD phosphorylation sites or the SBD SH3-binding motif were able to partially restore the migration response, while only a variant lacking both signaling functions was fully defective. Notably, the migration defects associated with p130Cas signaling-deficient variants correlated with longer FA lifetimes resulting from aborted FA disassembly attempts. However the SD mutational variant was fully defective in increasing actin assembly at the protruding leading edge and FA assembly/disassembly rates, indicating that SD phosphorylation is the sole p130Cas signaling function in regulating these processes. Our results provide the first quantitative evidence supporting roles for p130Cas SD tyrosine phosphorylation in promoting both leading edge actin flux and FA turnover during cell migration, while further revealing that the p130Cas SBD has a function in cell migration and sustained FA disassembly that is distinct from its known role of promoting SD tyrosine phosphorylation.